2013
DOI: 10.1007/s11274-013-1419-9
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts from kefir grains: isolation, identification, and probiotic characterization

Abstract: Kefir-a traditional beverage whose consumption has been associated with health benefits-is a logical natural product to investigate for new probiotic strains. The aim of the present work was to isolate and identify kefir yeasts and select those with acid and bile tolerance to study their adhesion to epithelial cells and their transit through mouse gut. From 4 milky and 3 sugary kefir grains, 34 yeast strains were isolated and identified by means of classical microbiological and molecular-genetic methods (whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 38 publications
12
97
0
10
Order By: Relevance
“…L. kefiri, L. kefiranofaciens and L. kefirgranum, which were proven by recent studies to have strong probiotic properties and positive health effects, are only present in kefir grains [14,15,16,17,18]. Moreover, the Saccharomyces and Kluyveromyces yeast strains unique to kefir grains also have important probiotic properties and antimicrobial effects that were observed in recent studies [19,20,21]. The reason for commercial kefir having a lower observed inhibitory effect is generally thought to be due to the fact that the starter culture microflora is very different from the original in commercial kefir.…”
Section: Resultsmentioning
confidence: 96%
“…L. kefiri, L. kefiranofaciens and L. kefirgranum, which were proven by recent studies to have strong probiotic properties and positive health effects, are only present in kefir grains [14,15,16,17,18]. Moreover, the Saccharomyces and Kluyveromyces yeast strains unique to kefir grains also have important probiotic properties and antimicrobial effects that were observed in recent studies [19,20,21]. The reason for commercial kefir having a lower observed inhibitory effect is generally thought to be due to the fact that the starter culture microflora is very different from the original in commercial kefir.…”
Section: Resultsmentioning
confidence: 96%
“…This yeast species is frequently associated with water kefir (3,4,10,13,14,19,20,51). Dekkera bruxellensis (anamorph Brettanomyces bruxellensis) was shown to be associated with water kefir only recently (3,20).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous microbial species in both kefir and kefir grains were identified using various microbiological and molecular techniques (Diosma, Romanin, Rey-Burusco, Londero, & Garrote, 2014;Gao, Gu, Abdella, Ruan, & He, 2012;Pogačić, Šinko, Zamberlin, & Samaržija, 2013). Dobson, O'Sullivan, Cotter, Ross and Hill (2011) investigated microbial species in kefir grains using high-throughput, sequence-based analysis.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
“…Grønnevik et al (2011) found that the LAB count in kefir samples decreased during the first 4 weeks of storage, whereas yeast levels increased throughout the storage period. Diosma et al (2014) isolated S. cerevisiae (15 strains), S. unisporus (six strains), Issatchenkia occidentalis (four strains) and K. marxianus (nine strains) from kefir grains. Uraz, Akkuzu, Özcan, and Sevimay (2012) detected C. kefyr and C. famata as the most abundant species in kefir samples.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%